Evaluation of angular and positional changes of maxillary third molars following premolar extraction, molar distalization, and non-extraction treatments - Zeynep Çoban Büyükbayraktar; Hasan Camcı; Sultan İçmen; Artun Yangın (BMC Oral Health)
Abstract Background To compare the effects of first premolar extraction, molar distalization, and non-extraction treatments on the angulation and vertical positions of maxillary second molars (MxM2s) and maxillary third molars (MxM3s). To our knowledge, this is the first study to compare the effects of three different treatment types on MxM3 simultaneously. Methods Initial (T0) and final (T1) panoramic radiographs of three different patient groups were analyzed: first premolar extraction group (n = 26 patients, 52 MxM2, 52 MxM3), molar distalization group (n = 20 patients, 40 MxM2, 40 MxM3), and non-extraction group (n = 31 patients, 62 MxM2, 62 MxM3). Descriptive data, including growth pattern, crowding, overjet, overbite, and maxillary incisor inclination, were recorded. Angular changes of maxillary third molars (MxM3) relative to the Interorbital Plane (IOP) and Palatal Plane (PP), as well as changes in inclination and vertical position according to Archer’s classification, were also documented. Differences between T0 and T1 within the same group were assessed using the paired sample t-test and Wilcoxon signed-rank test. Comparisons between groups were evaluated with one-way analysis of variance (ANOVA) and Kruskal-Wallis H test. The threshold for statistical significance was set at p < .05. Results IOP and PP values of MxM2 and MxM3 showed significant improvement in the extraction group (EG)(p < .001). The improvement in MxM3 IOP and PP values was not significant in the distalization group (DG)(p = .196 and p = .544, respectively). According to Archer’s classification, within-group comparisons revealed that the inclination and vertical position of MxM3 showed significant improvement in the EG, DG, and non-extraction groups (NEG)(inclination: p < .001 in EG, p = .032 in DG, p = .024 in NEG; vertical position: p < .001 in EG, p = .048 in DG, p < .001 in NEG). In between-group comparisons, the most significant improvement was observed in the EG. The number of MxM3 with vertical positions in Stages 1 and 2 at T1 were 19 in EG, 3 in DG, and 10 in NEG. Conclusion Premolar extraction has a positive effect on the angular and positional changes of MxM2 and MxM3. The changes in the inclination and vertical position of MxM3 between NEG and DG were not statistically significant.